The Approach to Servitization in the Czech Manufacturing Companies - Vlčková, Vladimíra; Podškubková, Lucie (UNIV HRADEC KRALOVE, 2020)
Nowadays servitization is an essential part of strategic marketing. Companies can build up a wide portfolio of conventional services, develop/acquire new services or offer advanced services closely connected with the product in the way they provide their customers with ability rather than with a physical value. Unlike foreign professional literature, term servitization appears in in the Czech professional literature sporadically only. It is possible to assume that insufficient cognizance of servitization also shows in the practice of manufacturing companies, i.e. that the service potential is not fully exploited. In this paper a research hypothesis that servitization is applied by manufacturing companies in the Czech Republic as a marketing tool rather than as a way to a change in their strategic focus has been constructed and discussed. The paper outcomes were drawn up based on the analysis, comparison, and synthesis of the information obtained (i) from a targeted research into the professional literature (ii) through an analysis of web pages of 165 selected companies from the point of view of services they offer and (iii) personal experience from interviews conducted at manufacturing companies. The outcomes then should help to identify the opportunities for servitization in manufacturing companies in the Czech Republic.
Přístup k servitizaci v českých výrobních společnostech
Keywords: servitization; services; manufacturing companies; differentiation of the offerings to customers; servitizace; služby; výrobní společnosti; diferenciace nabídek zákazníkům